Proposta de exposição museológica Estância Velha do Jarau patrimônio do Rio Grande do Sul: fronteira entre arqueologia, história e lenda - Linassi, Priscila Silva (2013)
This study deals with the formulation of a proposal exposure to archaeological collected Archaeological RS - Q -17 Estancia Velha Jarau . The survey collected information on bibliography , dissertations , monographs and material culture ; through these materials sought to develop a proposal for exposure. The purpose of this dissertation is to develop a proposal for the archaeological exhibition with the Estancia Velha Jarau . This thesis sought to examine initially the elements that make up the formation of the resort, as the pampa , his legend , the Archaeological Site , regarding the interventions , their archeology and the law of the same . After the discussion was contextualized , covering aspects such as museum, exhibition of goods , means of communication museum , as well as the proposed exhibition, pervaded by the Heritage Education . This contextualization sought to build a proposed museum exhibition meaningful , easy to understand , seeking access to information , preservation and enhancement of these assets , while important assets of Rio Grande do Sul and Brazil.